Coupling of PET waste electroreforming with green hydrogen generation using bifunctional catalyst - Li, Ying (2023)
Cost-effective and high-efficiency bifunctional electrocatalysts for electrooxidation of polyethylene terephthalate (PET) waste and green hydrogen generation are very crucial for practical implementation yet rarely reported. Herein, a bifunctional catalyst of cobalt modified nickel phosphide nanosheet arrays on nickel foam (Co-Ni2P/NF) for both PET hydrolysate oxidation reaction and hydrogen evolution reaction (HER) is reported, which is obtained by a facile hydrothermal and phosphidation treatment. The electrocatalyst is highly active for both PET hydrolysate oxidation reaction and HER with low overpotentials of 90 and 148 mV, respectively, to achieve a current density of 50 mA cm−2. By coupling PET hydrolysate oxidation reaction with HER, the assembled electrolyzer with Co-Ni2P/NF as a bifunctional catalyst only requires 1.43 V to afford 10 mA cm−2, much lower than that needed for pure water splitting (1.55 V). Complementary DFT study provides an in-depth understanding of HER and electrooxidation of PET on Co-Ni2P/NF. Our work suggests that electroreforming of abundant PET waste could be an energy-efficient and sustainable strategy for both plastic waste valorization and green hydrogen production via using a cost-effective and active bifunctional catalyst.